Evaluating LSP-TEOC.Pro: What we did and what we found out - Cullen, Joseph; Holloway, Gregory (Glottodidactica, 2025)
This article presents an evaluation of the LSP-TEOC.Pro project. It sets out the evaluation methodology applied, how it was implemented and the key evaluation findings. Given the exploratory nature of the project, the range and complexity of the intervening variables involved and logistical constraints, it was not possible to use an experimental evaluation approach. Instead, the evaluation used an approach based on a ‘realist’ and ‘theory-driven’ framework to test whether the ‘mechanisms’ implicit in the project theory of change were supported by the evidence. The evaluation showed that LSP-TEOC.PRO has progressed significantly along its ‘change journey’, although further effort is required going forward to support scaling up and out, so that the project has an impact at the macro level.